2019
DOI: 10.1016/j.ccell.2019.02.008
|View full text |Cite
|
Sign up to set email alerts
|

KRAS-IRF2 Axis Drives Immune Suppression and Immune Therapy Resistance in Colorectal Cancer

Abstract: Highlights d Oncogenic KRAS promotes an immune-suppressive profile in CRC d IRF2 is a key downstream target of oncogenic KRASmediating immune suppression d IRF2 suppresses MDSC migration and infiltration by targeting the CXCL3-CXCR2 axis d Enforced IRF2 expression or CXCR2 inhibition overcomes anti-PD1 resistance in CRC

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
356
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 411 publications
(375 citation statements)
references
References 64 publications
(85 reference statements)
18
356
0
1
Order By: Relevance
“…That is, a high expression of ELR (Glu–Leu–Arg) ‐positive CXC chemokines is not linked to tumor progression and worse prognosis in colorectal carcinoma in a linear fashion (Doll et al, ). In addition, W. Liao et al () found that CXCL3 was enhanced by KRAS‐IRF2 (interferon regulatory factor 2) axis, sequentially mediating immune suppression and immune therapy resistance in CRC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…That is, a high expression of ELR (Glu–Leu–Arg) ‐positive CXC chemokines is not linked to tumor progression and worse prognosis in colorectal carcinoma in a linear fashion (Doll et al, ). In addition, W. Liao et al () found that CXCL3 was enhanced by KRAS‐IRF2 (interferon regulatory factor 2) axis, sequentially mediating immune suppression and immune therapy resistance in CRC.…”
Section: Discussionmentioning
confidence: 99%
“…That is, a high expression of ELR (Glu-Leu-Arg)positive CXC chemokines is not linked to tumor progression and worse prognosis in colorectal carcinoma in a linear fashion (Doll et al, 2010). In addition, W. Liao et al (2019) found that CXCL3 was enhanced by KRAS-IRF2 (interferon regulatory factor 2) axis, CXCL8 (also known as IL-8), like CXCL3, also a member of the CXC chemokine family and a major mediator of the inflammatory response, primarily serves as a chemotactic factor by guiding the neutrophils to the site of infection. In the studies of cancer, many researchers considered that CXCL8 plays an extremely crucial part in tumor proliferation, invasion, migration, and tumor microenvironment in an autocrine or paracrine manner (Ha, Debnath, & Neamati, 2017;Liu et al, 2016;Matsuo et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Although KRAS mutations do not predict response to anti-PD-1, they are associated with reduced T cell infiltration, hinting that downstream pathways could regulate immunotherapy and may become relevant as additional combinations of immune checkpoint inhibitors enter the clinic. In this issue of Cancer Cell, Liao et al (2019) demonstrate that Kras G12D suppresses expression of interferon regulatory factor 2 (IRF2), a negative regulator of the CXCL3 chemokine expression ( Figure 1). This leads to enhanced recruitment of myeloid-derived suppressor cells (MDSCs) and restricted T cell accumulation, a resistance mechanism that limits response to anti-PD-1 therapy.…”
mentioning
confidence: 99%
“…Alterations of some top genes in our prediction, such as B2M, JAK1, JAK2, HSP90 , and IFNG , are known to be associated with poor response to anti-PD-1 therapy [7, 33-36]. Several genes that were recently found to be associated with anti-PD-1 response were also identified in the top list of our prediciton, such as KRAS [37], STK11 [38], DDR2 [39], and ATR [40].…”
Section: Resultsmentioning
confidence: 99%